Znaczenie intuicji językowej w procesie antycypacji – na przykładzie komunikacji obcojęzycznej - Wioletta A. Piegzik (Język. Religia. Tożsamość, 2021)
This paper presents the phenomenon of anticipation which is one of the manifestations of linguistic maturity and language user rationality. Anticipation, taking place essentially in implicit structures and based on evolutionary old intuition, improves speech comprehension and increases the efficiency of cognitive processes. The phenomenon in question is presented on the example of foreign language communication, because it is there that the mechanisms governing the formulation of accurate hypotheses about form and content are particularly evident.The first part of the article discusses speech perception, and with it the categorization and selection of an appropriate cognitive schema conditioning accurate anticipation. The second part presents factors that facilitate and hinder the right hypothesis. Finally, conclusions and directions for future research on anticipation are formulated.